A review on biological control of post-harvest fungal diseases of fruits - Rathod, Gulab (Current Botany, 2012)
A number of physical and chemical treatments have been evaluated for controlling post-harvest diseases. The physical treatment includes heat therapy, low temperature storage and radiation, while chemical treatment includes the use of chemical agents like antibiotics, growth regulators, fungicides, oils, chemicals and vapour emitting compounds. Biopesticides and their use in the control of plant diseases has become a modern trend in agriculture practice, which is termed as biological control. Biocontrol agents are found to be belonging to different groups of plants and microbes besides, which have been reported to be highly potent economical and eco-friendly for the successful control of plant pathogens.